The Relationship Between Learning Motivation and Learning Outcomes at Teratai Kindergarten in Kendari City - A. Nongko, Pahenra; Said, Hasmira; Amalia, Wa Ode Sari; Rohmiati; Salma, Sitti (Yayasan Sinergi Kawula Muda, 2025)
Learning motivation is a key factor that affects children's learning outcomes, including in early childhood education. This study aims to analyze the relationship between learning motivation and children's learning outcomes in Teratai Kindergarten, Kendari City. The research method uses a quantitative approach with a correlational design. The sample consisted of 30 class B children selected through purposive sampling technique. Data were collected using validated learning motivation questionnaires, as well as documentation of learning outcomes from student development reports. Data analysis was carried out by descriptive statistics, normality test, linearity test, and Pearson correlation test. The results showed a positive and significant relationship between learning motivation and children's learning outcomes (r = 0.682, p < 0.01). These findings indicate that children with higher levels of learning motivation tend to have better learning outcomes. Furthermore, it reinforces the view that learning strategies that promote intrinsic motivation, provide challenges appropriate to the child's development, and offer rewards for effort contribute to improved academic achievement. This study recommends the active role of teachers and parents in building a learning environment that supports children's motivation from an early age.